TRACKING DATA FLOW IN DISTRIBUTED COMPUTING SYSTEMS (2016)
A distributed computing environment comprises a plurality of distributed computer systems interconnected by one or more data networks. The plurality of distributed computer systems executes a plurality of applications. At least one of the distributed computer systems executes a data flow software tool that identifies potential data flows between the plurality of applications and generates a GUI that shows at least one upstream application and/or at least one downstream application for a subject application. The subject application can be selected by a user via the GUI; the at least one upstream application is an application that provides an incoming data flow to subject application; and the at least one downstream application is an application that receives an outgoing data flow from the subject application. In addition, the data flow software tool (when executed by the at least one computer system) receives, via the GUI, from the user, a first input for the at least one upstream application and/or a second input for the at least one downstream application. The first input comprises a verification that the at least one upstream application provides the incoming data flow to the subject application and the second input comprises a verification that the at least one downstream application receives the outgoing data flow from the subject application.